Pengembangan E-Modul Pola Busana Cad dengan Software Richpeace pada Mata Kuliah Pembuatan Pola dengan Komputer - Ramadhani, Yashinta; Sholikhah, Roudlotus; Wahyuningsih, Sri Endah; Atika, Atika (Fashion and Fashion Education Journal, 2024)
Abstract: Media is an important component in achieving learning objectives, as well as in the Computer Aided Pattern Making which studies CAD clothing pattern making using Richpeace software. This is a Research and Development (R&D) of analyzing the procedures and feasibility results of e-module development by testing the product results to expert judgment in the form of material experts and media experts. Methods of data collection using documentation and observation techniques. The development method takes the 5 Steps of Using the Research and Development Method from Sugiyono which consists of potentials and problems, data collection, product design, validation and revision. Based on the research that has been developed according to the procedure, the results are obtained in the form of an e-module as a way out of the problems that exist in the Computer Pattern Making Course. Assessment by material experts obtains an average proportion of 97.02% and is classified in the "Very Feasible" interpretation. The results of the assessment by media experts obtained an average proportion of 93.63% and classified in the interpretation of "Very Eligible". So it can be concluded that the E-Module for Making CAD Patterns Using Richpeace Software is very suitable for use as an alternative learning media in Pattern Making with Computer Courses Keyword: Instructional Media, e-modul development, CAD clothing pattern making, Richpeace Abstrak: Media menjadi salah satu komponen penting dalam tercapainya tujuan pembelajaran, begitu pula pada Mata Kuliah Pembuatan Pola dengan Komputer yang mempelajari pembuatan pola busana CAD menggunakan software Richpeace. Penelitian ini merupakan penelitian Research and Development (R&D) dengan tujuan untuk menganalisis prosedur dan hasil kelayakan pengembangan e-modul dengan mengujikan hasil produk kepada expert judgment berupa ahli materi dan ahli media. Metode pengumpulan data menggunakan teknik dokumentasi dan observasi. Metode pengembangan mengambil 5 Langkah Penggunaan Metode Penelitian dan Pengembangan dari Sugiyono yang terdiri dari potensi dan masalah, pengumpulan data, desain produk, validasi dan revisi. Berdasarkan penelitian yang telah dikembangkan sesuai prosedur diperoleh hasil berupa e-modul sebagai jalan keluar dari masalah yang ada pada Mata Kuliah Pembuatan Pola dengan Komputer. Penilaian oleh ahli materi diperoleh persentase rata-rata sebesar 97,02% dan tergolong dalam interpretasi “Sangat Layak”. Hasil penilaian oleh ahli media diperoleh persentase rata-rata sebesar 93,63% dan tergolong dalam interpretasi “Sangat Layak”. Sehingga dapat disimpulkan E-Modul Pembuatan Pola Busana CAD Menggunakan Software Richpeace sangat layak digunakan sebagai alternatif media pembelajaran pada Mata Kuliah Pembuatan Pola dengan Komputer. Kata Kunci : Media Pembelajaran, Pengembangan E-Modul, Pola busana CAD, Richpeace